2010
DOI: 10.1093/nar/gkq567
|View full text |Cite
|
Sign up to set email alerts
|

BspRI restriction endonuclease: cloning, expression in Escherichia coli and sequential cleavage mechanism

Abstract: The GGCC-specific restriction endonuclease BspRI is one of the few Type IIP restriction endonucleases, which were suggested to be a monomer. Amino acid sequence information obtained by Edman sequencing and mass spectrometry analysis was used to clone the gene encoding BspRI. The bspRIR gene is located adjacently to the gene of the cognate modification methyltransferase and encodes a 304 aa protein. Expression of the bspRIR gene in Escherichia coli was dependent on the replacement of the native TTG initiation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…The cloning and expression of CbeI in E. coli presented some challenges, as does the expression of other toxic genes including other restriction endonucleases [12, 24]. In addition to using BL21-CodonPlus(DE3)-RIPL cells to compensate for differences in codon usage between E. coli and C. bescii , we took advantage of the fact that CbeI is from an extreme thermophile and would be expected to have minimal activity at temperatures significantly below the growth temperature of C. bescii ( T opt ≈ 80°C).…”
Section: Discussionmentioning
confidence: 99%
“…The cloning and expression of CbeI in E. coli presented some challenges, as does the expression of other toxic genes including other restriction endonucleases [12, 24]. In addition to using BL21-CodonPlus(DE3)-RIPL cells to compensate for differences in codon usage between E. coli and C. bescii , we took advantage of the fact that CbeI is from an extreme thermophile and would be expected to have minimal activity at temperatures significantly below the growth temperature of C. bescii ( T opt ≈ 80°C).…”
Section: Discussionmentioning
confidence: 99%
“…A BLASTp search with the R.Gva14018I sequence found 39% identity and 57% similarity with the restriction endonuclease BspRI (GenBank CBE66553.1), a single protein with a known function among multiple matches. BspRI is an experimentally determined Type IIP REase that cleaves DNA at the sequence GGCC to produce blunt-end fragments [ 38 ]. Sequence analysis of R.Gva14018I using the PDEXK server [ 39 ] showed a probability of 0.95 that the nuclease belongs to the PD-(D/E)XK superfamily.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, similarity searches for M.Gva14018I showed many C-5 cytosine-specific DNA MTases, which generate GGm5CC methylation on both DNA strands. G. vaginalis ATCC 14018 possesses a HaeIII-like R-M system, which is widespread among bacterial species [ 38 , 40 , 43 ]. A HaeIII-like restriction endonuclease activity is an effective tool against foreign DNA because the short cleavage site frequently occurs [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that replacing the TTG initiation codon with an ATG codon resulted in high-level expression of a previously silent heterologous gene in E . coli [ 19 ]. To address the potential problems mentioned above selection of properly engineered recombinant host, silencing endogenous proteolytic enzymes or co-expression of cloned chaperons may highly stimulate recombinant protein production [ 20 ].…”
Section: Introductionmentioning
confidence: 99%